Study of Backup Power System Analysis (Emergency Generator) for Electricity Dision at West Sumatra Shipping Polytechnic - Tutur Winasis, Raden Roro Anggun; Ridal, Yani; Anshar, Chairul Nazalul (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the performance of the backup power system (emergency generator) at the West Sumatra Maritime Polytechnic. The reliability of the electricity supply is very important to support the continuity of educational activities and institutional operations. A backup power system is needed to anticipate power outages that can hamper these activities. This study was conducted using the method of literature study, field observation, interviews, documentation, and analysis of technical data obtained. That generator 1 received a load of 172.76 kVA (138.21 kW) and generator 2 of 294.62 kVA (235.70 kW), with a larger load distribution on Generator 2. The demand factor was 35.37% (generator 1) and 58.92% (generator 2), respectively, while the load factor was 0.35368 and 0.58924. These values indicate that the actual load has not reached the maximum capacity of the generator, so there is still a power reserve available. The utilization rate of generator 1 is 28.29% and generator 2 is 47.14%, which means both are still operating within safe limits, even though generator 2 is utilized more. During 5 hours of operation, fuel consumption is 225 liters and 255 liters, respectively, proportional to the size of the load carried. Voltage drops are still within the tolerance limit (?5%), namely 2.53 Volts on generator 1 and 2.40 Volts on generator 2. Power losses in the 360 mm² NYFGbY cable are also relatively small, namely 4.164 kW and 3.76 kW, which indicates the efficiency of the electrical system installation. Thus, the existing backup power system is still reliable and efficient, although further evaluation is needed for load distribution and performance optimization.